Latest Technological Advances with MCP-PMTs - Lehmann, Albert; Belias, A.; Dzhygadlo, R.; Gerhardt, A.; Lehmann, D.; Peters, K.; Schepers, G.; Schwarz, C.; Schwiening, J.; Traxler, M.; Schmitt, L.; Böhm, Merlin; et al. (Journal of Physics: Conference Series, 2022)
This paper discusses the most recent advances with 2-inch MCP-PMTs. The status in terms of lifetime, detection efficiency, rate capability, time resolution, and gain behavior in magnetic fields are summarized. Significant progress in collection (CE) and quantum efficiency (QE) led to an excellent detection efficiency DQE = QE∗CE of â1/430%. With a new DAQ setup up to several hundred anode pixels can be read out simultaneously in 3D allowing a glance "inside the PMT". Parameters like dark count rates and ion afterpulsing are measurable as a function of the incident photon position as well as the temporal and spacial spread of recoil electrons and electronic and charge-sharing crosstalk even inside a magnetic field.
CRIS-Team Scopus Importer:2022-12-30

Lifetime and performance of the very latest microchannel-plate photomultipliers - Miehling, Daniel; Böhm, Michael; Gumbert, Katja; Krauss, Steffen; Lehmann, Albert; Belias, A.; Dzhygadlo, R.; Gerhardt, A.; Lehmann, D.; Peters, K.; Schepers, G.; Schwarz, C.; et al. (Nuclear Instruments and Methods in Physics Research Section A: Accelerators, Spectrometers, Detectors and Associated Equipment, 2023)
The PANDA experiment at the FAIR facility at GSI will study hadron physics using a high intensity antiproton beam of up to 15 GeV/c momentum to perform high precision spectroscopy. Two DIRC detectors with their image planes residing in an ∼1T magnetic field will be used in the experiment. The only suitable photon detectors for both DIRCs were identified to be Microchannel-Plate Photomultipliers (MCP-PMTs). Since the aging problems of MCP-PMTs were solved recently by coating the MCPs with the so-called ALD-technique (atomic layer depostion) we are investigating devices which are significantly improved with respect to other parameters, as, e.g., the collection efficiency (CE) and the quantum efficiency (QE). The latest generation of MCP-PMTs can reach a detective quantum efficiency DQE=QE⋅CE of 30%. This paper will present the performance of the most advanced 53 × 53 mm2 ALD-coated MCP-PMTs from Photonis (8 × 8 and 3 × 100 anodes) and Photek (8 × 8 anodes), also inside the magnetic field. With a picosecond laser and a multi-hit capable DAQ system which allows read out up to 300 pixels simultaneously, parameters like darkcount rate, afterpulse probability and time resolution can be investigated as a function of incident photon position.
CRIS-Team Scopus Importer:2023-06-02
Keywords: Atomic layer deposition (ALD); Cherenkov detectors; Lifetime; Microchannel-plate photomultipliers

Performance of the most recent Microchannel-Plate PMTs for the PANDA DIRC detectors at FAIR - Krauss, Steffen; Böhm, Merlin; Gumbert, Katja; Lehmann, Albert; Miehling, Daniel; Belias, A.; Dzhygadlo, R.; Gerhardt, A.; Lehmann, D.; Peters, K.; Schepers, G.; Schwarz, C.; et al. (Nuclear Instruments and Methods in Physics Research Section A: Accelerators, Spectrometers, Detectors and Associated Equipment, 2023)
In the PANDA experiment at the FAIR facility at GSI two DIRC (Detection of Internally Reflected Cherenkov light) detectors will be used for π/K separation up to 4 GeV/c. Due to their location in a high magnetic field and other stringent requirements like high detection efficiency, low dark count rate, radiation hardness, long lifetime and good timing, MCP-PMTs (microchannel-plate photomultiplier) were the best choice of photon sensors for the DIRC detectors in the PANDA experiment. This paper will present the performance of some of the latest 2 × 2 inch 2 MCP-PMTs from Photek and Photonis, including the first mass production tubes for the PANDA Barrel DIRC from Photonis. Performance parameters like the collection efficiency (CE), quantum efficiency (QE), and gain homogeneity were determined. The effect of magnetic fields on some properties like gain and charge cloud width was investigated as well. Apart from that the spatial distribution of many internal parameters like time resolution, dark count rate, afterpulse ratio, charge sharing crosstalk and recoil electrons were measured simultaneously with a multihit capable DAQ system. The latest generation of Photonis MCP-PMTs shows a unexpected ”escalation” effect where the MCP-PMT itself produces photons.
CRIS-Team Scopus Importer:2023-10-06
Keywords: Atomic layer deposition (ALD); DIRC; MCP-PMT; Microchannel-plate; PANDA; Photomultiplier

Systematic approach to measure the performance of microchannel-plate photomultipliers - Lehmann, Albert; Böhm, Merlin; Götz, Klaus; Gumbert, Katja; Krauss, Steffen; Miehling, Daniel; Pfaffinger, Markus (Nuclear Instruments and Methods in Physics Research Section A: Accelerators, Spectrometers, Detectors and Associated Equipment, 2024)
In this paper, we present our approach to systematically measure numerous performance parameters of microchannel plate photomultiplier tubes. The experimental setups, the analyses and selected results are discussed. Although the techniques used may be different in other locations, the document is intended as a guide for comparable measurements with other types of microchannel plate photomultiplier tubes. Measurements are shown for the following performance parameters: spectral and spatial quantum efficiency, collection efficiency, gain as a function of voltage, position and magnetic field, time resolution, rate capability and lifetime. By using a dedicated 3-axis stepper and an FPGA-based data acquisition system, also inner PMT parameters are measured as a function of the active area, such as relative detection efficiency, dark count rate, time resolution, recoil electron and afterpulse distributions, as well as charge sharing and electronic crosstalk. In addition, some of the parameters are investigated inside a strong magnetic field. For many of these measurements, the change of most setup parameters and the subsequent analysis can be controlled semi-automatically by software scripts.
CRIS-Team Scopus Importer:2024-07-19
Keywords: Afterpulses; Collection efficiency; Crosstalk; Dark count rate; Gain; Lifetime; Magnetic field; Multianode microchannel-plate PMTs; PANDA; Performance parameters; Quantum efficiency; Rate capability; Recoil electrons; Time resolution

The PANDA Barrel DIRC - Dzhygadlo, R.; Belias, A.; Gerhardt, A.; Lehmann, D.; Peters, K.; Schepers, G.; Schwarz, C.; Schwiening, J.; Traxler, M.; Wolf, Y.; Schmitt, L.; Böhm, Merlin; et al. (Nuclear Instruments and Methods in Physics Research Section A: Accelerators, Spectrometers, Detectors and Associated Equipment, 2023)
The PANDA experiment at the international accelerator Facility for Antiproton and Ion Research in Europe (FAIR), Darmstadt, Germany, will address fundamental questions of hadron physics using p̄p annihilations. Excellent Particle Identification (PID) over a large range of solid angles and particle momenta will be essential to meet the objectives of the rich physics program. Charged PID in the target region will be provided by a Barrel DIRC (Detection of Internally Reflected Cherenkov light) counter. The Barrel DIRC, covering the polar angle range of 22–140 degrees, will provide a π/K separation power of at least 3 standard deviations for charged particle momenta up to 3.5 GeV/c. The design of the Barrel DIRC features narrow radiator bars made from synthetic fused silica, an innovative multi-layer spherical lens focusing system, a prism-shaped synthetic fused silica expansion volume, and an array of lifetime-enhanced Microchannel Plate PMTs (MCP-PMTs) to detect the hit location and arrival time of the Cherenkov photons. Detailed Monte-Carlo simulations were performed, and reconstruction methods were developed to study the performance of the system. All critical aspects of the design and the performance were validated with system prototypes in a mixed hadron beam at the CERN PS. In 2020 the PANDA Barrel DIRC project advanced from the design stage to component fabrication. The series production of the fused silica bars was successfully completed in 2021 and delivery of the MCP-PMTs started in May 2022.
CRIS-Team Scopus Importer:2023-07-21
Keywords: Cherenkov counter; DIRC; Particle identification; Ring imaging